Cholangiocyte organoids for disease, cancer, and regenerative medicine - Munemasa Nagao; Akihisa Fukuda; Hirotaka Kashima; Sho Matsuyama; Kei Iimori; Shinnosuke Nakayama; Kenta Mizukoshi; Munenori Kawai; Go Yamakawa; Mayuki Omatsu; Mio Namikawa; Tomonori Masuda; et al. (European Journal of Cell Biology)
The biliary tract is a ductal network comprising the intrahepatic (IHBDs) and extrahepatic bile duct (EHBDs). Biliary duct disorders include cholangitis, neoplasms, and injury. However, the underlying mechanisms are not fully understood. With advancements in 3D culture technology, cholangiocyte organoids (COs) derived from primary tissues or induced pluripotent stem cells (iPSCs) can accurately replicate the structural and functional properties of biliary tissues. These organoids have become powerful tools for studying the pathogenesis of biliary diseases, such as cystic fibrosis and primary sclerosing cholangitis, and for developing new therapeutic strategies for cholangiocarcinoma. Additionally, COs have the potential to repair bile duct injuries and facilitate transplantation therapies. This review also discusses the use of organoids in genetically engineered mouse models to provide mechanistic insights into tumorigenesis and cancer progression. Continued innovation and standardization of organoid technology are crucial for advancing precision medicine for biliary diseases and cancer.